2010
DOI: 10.1007/s13225-009-0009-5
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic diversity of culturable fungi from the deep-sea sediments of the Central Indian Basin and their growth characteristics

Abstract: Very few studies have addressed the diversity of culturable fungi from deep-sea sediments. We are reporting here the diversity of culturable fungi in deep-sea sediments of the Central Indian Basin obtained from a depth of ∼5,000 m. A total of 16 filamentous fungi and 12 yeasts isolated from 20 sediment cores of ∼35 cm length were identified by 18S and ITS sequencing of SSU rDNA. Most of the filamentous fungi were Ascomycota, while two were Basidiomycota. Microscopic identification of sporulating cultures mostl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
89
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 33 publications
(41 reference statements)
9
89
0
Order By: Relevance
“…Fungi isolated from deep seas were first reported nearly 50 years ago (Roth et al 1964), then a great number of fungi including some novel species have been published by both conventional culture-dependent (Raghukumar et al 2004; Gadanho and Sampaio 2005; Damare et al 2006; Nagahama et al 2006; Le Calvez et al 2009; Singh et al 2010) and culture-independent methods (Lai et al 2007; Le Calvez et al 2009; Nagano et al 2010). Le Calvez et al (2009) reported striking differences in their comparison of deep-sea fungal diversity assessed by culture-dependent and culture-independent methods.…”
Section: Cold-adapted Fungi and Their Living Strategiesmentioning
confidence: 99%
“…Fungi isolated from deep seas were first reported nearly 50 years ago (Roth et al 1964), then a great number of fungi including some novel species have been published by both conventional culture-dependent (Raghukumar et al 2004; Gadanho and Sampaio 2005; Damare et al 2006; Nagahama et al 2006; Le Calvez et al 2009; Singh et al 2010) and culture-independent methods (Lai et al 2007; Le Calvez et al 2009; Nagano et al 2010). Le Calvez et al (2009) reported striking differences in their comparison of deep-sea fungal diversity assessed by culture-dependent and culture-independent methods.…”
Section: Cold-adapted Fungi and Their Living Strategiesmentioning
confidence: 99%
“…Our characterization of artificial reef fungal biofilm communities represents the first step towards understanding the fungal component of microbial diversity of hard substrata within the MS Sound, an economically productive estuary for fisheries including shellfish. Considering the increasing number of reports on the occurrence of marine fungi and their involvement in detrital processing, it can be concluded that the current microbial loop model neglects the role of fungi in the processing of organic matter in marine environments (Hyde et al 1998, Singh et al 2010, Gutiérrez et al 2011, Mouton et al 2012). Further research is needed to determine fungal roles in marine ecological processes in hopes of providing a more complete model of organic material degradation in coastal ecosystems, foundational to food webs and nutrient cycling (Gutiérrez et al 2011, Mouton et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…To isolate micromycetes from marine sediments, different culture conditions have been tested such as agar types, atmospheric pressure (1-1200 bars), temperatures (5°C or 30 °C) and light or darkness (Roth et al 1964;Damare et al 2006;Singh et al 2010;Singh et al 2012). A greater number of fungi being isolated has been achieved using MEA (Malt Extract Agar) diluted to 1:5, 200 bar and 5°C.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we used YEPD agar at 100% concentration, and darkness, as these conditions were favorable for the isolation of micromycetes from marine sediments in comparison to other works. Singh et al (2010) reported 28 micromycetes from 496 sediments, while Damare et al (2006) isolated 181 micromycetes from 672 sediments. All these studies were carried out in the central basin of India by Roth et al (1964) and Singh et al (2010) suggest that the difference in the frequency of micromycetes recovery may be due to the oceanographic conditions where the sediments were collected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation